HUBUNGAN FAKTOR RISIKO DENGAN PENYAKIT GAGAL GINJAL KRONIK DI UNIT HEMODIALISA - Sari, Young; Simanjuntak, Salomo; Hutasoit , Eka Samuel P. (Jurnal Kedokteran Methodist, 2019)
Background : Chronic kidney disease (CKD) is kidney damage and / or decrease in GFR (Glomerulus Filtration Rate) less than 60mL / min / 1.73m2 for at least 3 months. Chronic kidney disease can be caused by several risk factors such as hypertension, diabetes mellitus, chronic pyelonephritis, obstructive nephropathy, and other causes. The purpose of this study was to determine the relationship between risk factors and chronic renal failure in the hemodialysis unit. Method : The research method used is a Literature Review, using secondary data. Data were collected using documentation techniques. The research journals used were 12 journals with inclusion criteria for the publication date of the last 10 years, the language used was Indonesian or English, with the research subjects of patients with a diagnosis of chronic renal failure, and full text publication. Conclusion : Hypertension and diabetes mellitus are the most dominant risk factors for chronic renal failure.